1991
DOI: 10.1128/mcb.11.5.2335
|View full text |Cite
|
Sign up to set email alerts
|

Structure of the gene encoding VGF, a nervous system-specific mRNA that is rapidly and selectively induced by nerve growth factor in PC12 cells.

Abstract: Nerve growth factor (NGF) plays a critical role in the development and survival of neurons in the peripheral nervous system. Following treatment with NGF but not epidermal growth factor, rat pheochromocytoma (PC12) cells undergo neural differentiation. We have cloned a nervous system-specific mRNA, NGF33.1, that is rapidly and relatively selectively induced by treatment of PC12 cells with NGF and basic fibroblast growth factor in comparison with epidermal growth factor. Analysis of the nucleic acid and predict… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

7
108
0

Year Published

1997
1997
2013
2013

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 125 publications
(115 citation statements)
references
References 109 publications
(150 reference statements)
7
108
0
Order By: Relevance
“…Surprisingly, however, the VGF mRNA in the NGF-embedded composite group showed a three-fold higher level of expression compared with the 50 ng/mL NGF group on day 2. Our results demonstrated that VGF mRNA levels were maximally induced to ~16-fold, which was in agreement with a previous report [22]. However, polarization can also lead to a rapid increase in VGF mRNA expression level by triggering calcium influx through voltage-gated calcium channels [22,23].…”
Section: Mrna Expression Levels Of Cell Differentiationrelated Genessupporting
confidence: 93%
See 1 more Smart Citation
“…Surprisingly, however, the VGF mRNA in the NGF-embedded composite group showed a three-fold higher level of expression compared with the 50 ng/mL NGF group on day 2. Our results demonstrated that VGF mRNA levels were maximally induced to ~16-fold, which was in agreement with a previous report [22]. However, polarization can also lead to a rapid increase in VGF mRNA expression level by triggering calcium influx through voltage-gated calcium channels [22,23].…”
Section: Mrna Expression Levels Of Cell Differentiationrelated Genessupporting
confidence: 93%
“…Our results demonstrated that VGF mRNA levels were maximally induced to ~16-fold, which was in agreement with a previous report [22]. However, polarization can also lead to a rapid increase in VGF mRNA expression level by triggering calcium influx through voltage-gated calcium channels [22,23]. During the degradation of the composites, β-TCP elevates the calcium concentration in the culture medium, which is involved in mediating the growth and migratory direction of axons.…”
Section: Mrna Expression Levels Of Cell Differentiationrelated Genessupporting
confidence: 93%
“…82,83 We failed to show association to any of the candidate genes according to the dichotomized clinical diagnosis of schizophrenia and schizophrenia spectrum disorders among 245 schizophrenia families, originating from the same geographical region as the families revealing the linkage to 7q21-32. With the markers used, we had fairly good coverage of the allelic diversity of the four studied genes.…”
Section: Association Of Reelin With Working Memorymentioning
confidence: 74%
“…A related series of constructs was made by truncating the full-length HA-tagged VGF using PCR primers to introduce termination codons following amino acids 177, 282, 367, 480, and 543 of rat VGF. The VGF:GFP constructs, which directly fuse VGF and GFP sequences in the vector pcDNA3 (Invitrogen) at the indicated sites, were created by PCR using pEGFP-N1 and the rat VGF cDNA (7,16) as templates. Sequences of all PCR-generated fragments were verified.…”
Section: Methodsmentioning
confidence: 99%
“…Secreted via the Regulated Release Pathway-VGF can be differentially processed, and the C terminus is rich in paired basic amino acids (7,9,16). Additionally, N-terminal signal peptide sequences and loop structures have been implicated in sorting, so two series of plasmids that contained either N-or C-terminal modifications were constructed.…”
Section: Vgf and Epitope-tagged Vgf Are Localized In Ldcvs Andmentioning
confidence: 99%